Crustal structure and its tectonic implications beneath the middle–lower Yangtze metallogenic belt in Anhui Province: 3D deep seismic sounding results from airgun source in inland waters - Guo, Wenbin; Yang, Zhuoxin; Tian, Xiaofeng; Liu, Baofeng; Zheng, Chenglong; Song, Xianghui; Gao, Zhanyong; Qiu, Yong (Frontiers in Earth Science, 2023)
To evaluate the effectiveness of using airguns as seismic sources in inland waters to detect the regional crustal structure, a mobile large-capacity airgun excitation experiment was conducted in October 2015 in the Anhui section of the middle–lower Yangtze metallogenic belt. In this study, we extracted 1,957 first-arrival phases (Pg) and 2,179 Moho reflection phases (PmP) from the airgun seismic signals, and performed joint inversion of the traveltimes. The inversion results reveal the P-wave high-velocity anomalies above 7km depth in the upper crust beneath the ore clustering areas, suggesting the source of mineralized materials. The crustal velocity structure characteristics substantially differed above and below a depth of 7 km, indicating the existence of a regional basement detachment surface. The velocity structure in the middle–lower crust, especially in the lower crust show lateral uniformity characteristic, which could be related to that the middle–lower Yangtze metallogenic belt had undergone a MASH metallization process. The Moho is 30–36 km deep, and its uplift zone extends from southwest to northeast in a “V” shape, which is consistent with the planar spreading characteristics of the metallogenic belt, indicating that the asthenosphere uplift and crustal thinning have had a controlling effect on the formation of the metallogenic belt. This study suggests the present-day crust in the region along the Yangtze River in Anhui retains the traces of lithosphere delamination-thinning and basaltic magma underplating during the Yanshan period. Our results indicates that airgun source detection in inland waters can effectively determine the continental crustal structure.